Analogue Modeling of Oblique Convergent Strike-Slip Faulting and Application to The Seram Island, Eastern Indonesia - Benyamin Sapiie; Meli Hadiana (Geological Agency, 2014)
DOI:10.17014/ijog.v1i3.189Sandbox experiment is one of the types of analogue modeling in geological sciences in which the main purpose is simulating deformation style and structural evolution of the sedimentary basin. Sandbox modeling is one of the effective ways in conducting physically modeling and evaluates complex deformation of sedimentary rocks. The main purpose of this paper is to evaluate structural geometry and deformation history of oblique convergent deformation using of integrated technique of analogue sandbox modeling applying to deformation of Seram Fold-Thrust-Belt (SFTB) in the Seram Island, Eastern Indonesia. Oblique convergent strike-slip deformation has notoriously generated area with structural complex geometry and pattern resulted from role of various local parameters that control stress distributions. Therefore, a special technique is needed for understanding and solving such problem in particular to relate 3D fault geometry and its evolution. The result of four case (Case 1 to 4) modeling setting indicated that two of modeling variables clearly affected in our sandbox modeling results; these are lithological variation (mainly stratigraphy of Seram Island) and pre-existing basement fault geometry (basement configuration). Lithological variation was mainly affected in the total number of faults development. On the other hand, pre-existing basement fault geometry was highly influenced in the end results particularly fault style and pattern as demonstrated in Case 4 modeling. In addition, this study concluded that deformation in the Seram Island is clearly best described using oblique convergent strike-slip (transpression) stress system.